Extension in popular environmental education: chores in the work community (2021)
This article is the result of doctoral research in Education, which sought to understand the Popular Extension in Environmental Education, experienced by a Work Community, in the city of Uberaba, Minas Gerais, Brazil. It aims to present the educational processes linked to what to do in popular environmental education. Data collection took place through participant observation and data were analyzed based on content analysis. It was possible to understand that all the people involved and committed to the transformation of that reality experienced in and by the work community, become environmental educators, through their most varied what to do. Thus, an environmental educator is a mediator of the understanding of the relations that the community (s) in which she is inserted with the environment, so that Popular Environmental Education is in tune with the spirit of a popular extension of character. educational and transformative, based on a participatory methodology that allows the development of a practice in which the people involved seek the construction and systematization of knowledge that lead them to consciously focus on reality.